Do human osteoblasts grow into open-porous titanium? - U Müller; T Imwinkelried; M Horst; M Sievers; U Graf-Hausner (European Cells & Materials, 2006)
A titanium foam for spine fusion and other applications was tested by cell culture. Its high porosity and surface roughness should enable bone cells to grow through it, resulting in a better fixation of the vertebral body.The foam was tested by in vitro experiments with human osteoblasts under static culture conditions and in a perfused system. By means of cell number, viability, scanning electron microscopy and histological staining, cell proliferation could be observed. The expression of osteogenic genes like collagen-I, alkaline phosphatase and osteocalcin was proven by reverse transcription polymerase chain reaction (RT-PCR) as well as in the case of alkaline phosphatase with biochemical methods.The conducted experiments showed that human osteoblasts could grow through the interconnected porosity of the metal foam and that they expressed an osteoblast like phenotype. The results suggest that in vivo osteoblasts are likely to form a trabecular bone bridge through this titanium foam. Consequently, with this osteoconductive material, there may be a reduced need for autologous bone in spinal fusion procedures.